Монгол хэлний “өөрөөр хэлбэл” гэдэг холбох үгийн бүтэц, утга, үүрэг, хэрэглээ - Пүрэв-Очир, Б. (Acta Mongolica, 2005)
Author studied in his academic article particular issues on structure, meaning, function, identity and various stylistic usage of a connective word “in other words” in modern Mongolian language. Subject was studied and based on rich statements of exposition, cogitation, enumeration and narration and following several conclusions were drawn. They are: 1. A compound structured connective word “in other words” in Mongolian language is used on parenthical coordination and it is an analytic means which links perfect and imperfect units. 2. A connective word “or” mainly denotes nominal phrase that has stagnant property but “in other words’Veepeep xsnSsn/ links verbal phrase, which has unprogressive property. 3. When two units in determinative-determined relation are connected in syntactic, morphological and textual level, attribute is detected from speech aspect and mostly units that are explained in different meaning are detected such as extended, short, emphasized, unemphasised, unsimplified...etc., 4. It can be considered, to replace and accent on explaining any perfect and imperfect units to each is associated with a dynamic conversion which is carried in related situation on syntactic level. 5. When perfect and imperfect units are connected with “in other words” similar , contrasted, paranomic meant units are derived and conversions are carried. 6. “In other words” in Mongolian language is a special connective word, which mainly used in contexts of exposition, cogitation, enumeration and links replaced elements.